Preparation of high-capacity silicon-carbon composite negative electrode material

Through nano-processing of photovoltaic waste silicon powder and design of multi-layer buffer structure, the problems of high cost and unstable performance in the preparation of silicon-carbon composite materials were solved, and the preparation of efficient and stable lithium-ion battery negative electrode materials was achieved.

CN120646766APending Publication Date: 2025-09-16湖州启源金灿新能源科技有限公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510858126.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-25
Publication Date
2025-09-16

AI Technical Summary

Technical Problem

The existing preparation methods of silicon-carbon composite negative electrode materials have problems such as complex processes, high costs, and difficulty in accurately controlling the silicon-carbon ratio and microstructure, resulting in unstable material performance and difficulty in meeting the needs of large-scale industrial production.

Method used

Photovoltaic waste silicon powder is converted into nano-scale silicon particles using electronic-grade hydrochloric acid pickling combined with ball milling under nitrogen protection. A calcium carbonate core-shell structure and a gradient carbon coating layer are constructed, combined with a carbon nanotube conductive network and a graphene nanoribbon composite material to form a multi-layer buffer structure, thereby improving the stability and electrical conductivity of the material.

Benefits of technology

It achieves low-cost, environmentally friendly nano-processing, alleviates the volume expansion problem of silicon, improves the structural stability and electrical conductivity of the material, and enhances the cycle stability and rate performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120646766A_ABST
    Figure CN120646766A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a high-capacity silicon-carbon composite negative electrode material, which comprises the following steps: preparation of electronic-grade hydrochloric acid, preparation of a photovoltaic waste silicon powder ball mill, preparation of a silicon-coated calcium carbonate core-shell structure material, preparation of a gradient carbon coating layer, synthesis preparation of a carbon nanotube conductive network, preparation of a graphene nanobelt silicon-carbon composite material and the like. The preparation method creatively combines a two-step electrostatic attraction self-assembly method, a high-temperature oxidation process and other preparation methods, the prepared silicon-carbon composite material shows stable cycle performance and high capacity performance, and the silicon-carbon composite material has the advantages of high specific capacity and low impedance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the preparation of a high-capacity silicon-carbon composite negative electrode material. Background Art

[0002] Driven by the surge in global demand for clean energy and the concept of sustainable development, the new energy industry is booming. Lithium-ion batteries, due to their high energy density and long cycle life, are widely used in electronic devices, electric vehicles, and large-scale energy storage. Anode materials are the core of lithium-ion batteries. Silicon materials have a theoretical specific capacity of up to 4200mAh / g, approximately 11 times that of graphite anodes, making them extremely promising for application. However, silicon expands by up to 300% when lithium is inserted, leading to structural pulverization and electrical contact failure. Furthermore, their low intrinsic conductivity affects charge and discharge rates, limiting their practical applications.

[0003] To effectively address the aforementioned issues with silicon materials, silicon-carbon composite materials have emerged. Carbon materials can not only buffer the volume changes of silicon during the charge and discharge process, but can also significantly improve the electrical conductivity of the composite material, thereby enhancing the battery's cycle stability and rate performance. Although silicon-carbon composite anode materials show promising application prospects, existing preparation methods still have many shortcomings. Some preparation processes are complex and require the use of expensive equipment and reagents, resulting in high production costs; some preparation processes make it difficult to precisely control the ratio of silicon to carbon and the microstructure, resulting in uneven material performance and making it difficult to meet the needs of large-scale industrial production. Therefore, it is of great practical significance to develop a method for preparing high-capacity silicon-carbon composite anode materials with a simple preparation process, controllable costs, and the ability to precisely control the silicon-carbon ratio and microstructure. By overcoming this technical challenge, it is expected to further enhance the performance of lithium-ion batteries and help the new energy industry achieve more efficient and sustainable development. Summary of the Invention

[0004] In order to solve the above problems, the present invention provides a method for preparing a high-capacity silicon-carbon composite negative electrode material.

[0005] The present invention relates to the preparation of a high-capacity silicon-carbon composite negative electrode material, comprising the following steps: preparation of electronic-grade hydrochloric acid, preparation by ball milling of photovoltaic waste silicon powder, preparation of a silicon@calcium carbonate core-shell structure material, preparation of a gradient carbon coating layer, preparation of a carbon nanotube conductive network synthesis, and preparation of a graphene nanoribbon silicon-carbon composite material.

[0006] Preferably, in step (1), electronic grade hydrochloric acid is prepared Using trichloroethylene (TCE) and hydrofluoric acid (AHF) as raw materials, a fluorination reaction is carried out in a certain ratio to generate hydrogen chloride (HCl) as a by-product. The reaction products are separated by a distillation tower, and high-purity hydrogen chloride gas is separated from the top of the tower and fed into a scrubbing tower. The scrubbing tower uses a circular hole block graphite falling film absorber. The top temperature of the scrubbing tower is controlled below zero. In the scrubbing tower, the hydrogen chloride gas contacts and absorbs low-concentration hydrochloric acid from the bottom of the tail gas tower. After screening, electronic-grade hydrochloric acid is obtained. Step (2) Preparation of nano-sized ball-milled waste silicon powder particles First, the pre-treated photovoltaic waste silicon powder is acid-washed and purified with the electronic-grade hydrochloric acid in step (1), and vacuum-dried for a period of time, and then ball-milled for a period of time under a protective atmosphere of N2 to obtain nano-sized ball-milled waste silicon powder particles; Step (3) Preparation of silicon@calcium carbonate core-shell structure material Take a small amount of the waste silicon powder particles obtained by ball milling in step (2) and calcium carbonate, and prepare a certain amount of sodium carbonate solution and calcium chloride solution in a certain mass ratio. Then, disperse the waste silicon powder particles in a certain amount of sodium carbonate solution to prepare a mixed solution Si / NaCO3. Then, drop Si / NaCO3 into a certain amount of calcium chloride solution while maintaining a constant temperature and a suitable water bath temperature. Finally, repeatedly filter, wash and dry to obtain a silicon@calcium carbonate core-shell structure material. Step (4) Preparation of gradient carbon coating layer According to a certain mass ratio, a certain amount of citric acid and the silicon@calcium carbonate core-shell structure of step (3) are prepared respectively, and the mixture is dispersed in an alcohol solution and continuously stirred to obtain a mixed solution. The mixed solution is placed in a water bath at a certain temperature to evaporate the alcohol, and then the evaporated mixture is placed in a tubular furnace at a certain temperature for heat treatment and calcination for a period of time. Finally, the calcined mixture is pickled with dilute hydrochloric acid for a period of time, and repeatedly filtered, washed, and dried to obtain a gradient carbon coating layer construction material; Step (5) Preparation of carbon nanotube conductive network synthesis The gradient carbon coating layer construction material of step (4), a certain amount of nano-sized ball-milled waste silicon powder particles prepared in step (2) and an appropriate amount of hexadecyl ammonium bromide (CTAB) are added together in deionized water and ultrasonically treated to obtain a suspension, and then CNTs are added and continued to be stirred and dried, and sintered at high temperature in an N2 atmosphere to obtain a carbon nanotube conductive network; Step (6) Preparation of graphene nanoribbon silicon-carbon composite material According to a certain ratio, the carbon nanotube conductive network material of step (5) and the gradient carbon coating layer construction material (silicon-carbon composite material) of step (4) are added to deionized water to obtain a solution, an appropriate amount of chitosan solution is added, and the precursor is obtained by centrifugal drying. Finally, the precursor is sintered at a high temperature under a protective atmosphere of N2 to obtain a graphene nanoribbon silicon-carbon composite material.

[0007] Preferably, in step (1), electronic grade hydrochloric acid is prepared Using trichloroethylene (TCE) and hydrofluoric acid (AHF) as raw materials, a fluorination reaction is carried out in a ratio of 1-5:2-7 to generate hydrogen chloride (HCl) as a by-product. The reaction products are separated by a distillation tower, and high-purity hydrogen chloride gas is separated from the top of the tower and fed into a scrubbing tower. The scrubbing tower adopts a circular hole block graphite falling film absorber with an operating pressure range of 0-60kPa and an operating temperature range of -25-80℃. The top temperature of the scrubbing tower is controlled at -35--25℃, the pressure is controlled at 0.9-1.1MPa, and the temperature difference is controlled at 0-5℃. In the scrubbing tower, the hydrogen chloride gas contacts and absorbs low-concentration hydrochloric acid from the bottom of the tail gas tower. After screening, electronic-grade hydrochloric acid is obtained.

[0008] As a preference, step (2) preparation of nano-sized ball-milled waste silicon powder particles First, the pretreated photovoltaic waste silicon powder is acid-washed and purified with the electronic-grade hydrochloric acid in step (1) for 20 to 24 hours, vacuum-dried for 10 to 12 hours, and then ball-milled for 2 to 4 hours under a protective atmosphere of N2 to obtain nano-sized ball-milled waste silicon powder particles.

[0009] The advantage of adopting the present invention is that no hazardous chemicals are required in this step. Photovoltaic waste silicon powder is industrial waste, low-cost and environmentally friendly. Through electronic-grade hydrochloric acid pickling and purification combined with ball milling under nitrogen protection, the photovoltaic waste silicon powder is converted into nano-scale silicon particles. The nano-processing significantly reduces the size of the silicon particles, effectively alleviates the volume expansion problem, and provides a highly active silicon source for subsequent composite material preparation.

[0010] As a preference, step (3) preparation of silicon@calcium carbonate core-shell structure material Take 0.5~2g of the nano-sized ball-milled waste silicon powder particles in step (2) and calcium carbonate in a mass ratio of 1~5:1~5 to prepare 80~100mL of sodium carbonate solution and calcium chloride solution. Then, disperse the waste silicon powder particles in 80~100mL of sodium carbonate solution to prepare a mixed solution Si / NaCO3. Then, drop Si / NaCO3 into 80~100mL of calcium chloride solution while maintaining a constant temperature. The water bath temperature is at 30~50℃. Finally, filter, wash and dry repeatedly to obtain a silicon@calcium carbonate core-shell structure material.

[0011] The advantage of adopting the present invention is that, in this step, a calcium carbonate shell is constructed on the surface of the silicon particles through the precipitation reaction of sodium carbonate and calcium chloride solution. The core-shell structure forms a physical barrier, buffering the volume expansion of silicon and improving the structural stability of the material. At the same time, the neutral environment and porous properties of calcium carbonate facilitate electrolyte penetration, optimize lithium ion transmission efficiency, and provide a base for subsequent carbon coating.

[0012] As a preference, step (4) the preparation of the gradient carbon coating layer According to the mass ratio of 1~5:1~5, citric acid and the silicon@calcium carbonate core-shell structure of step (3) are prepared in a mass ratio of 0.5~2:1~3, mixed and dispersed in an alcohol solution and continuously stirred to obtain a mixed solution, the mixed solution is placed in a water bath at 80~100℃ to evaporate the alcohol, and then the evaporated mixture is placed in a tube furnace at 500~800℃ for heat treatment and calcination for 2~5h. Finally, the calcined mixture is pickled with dilute hydrochloric acid for 20~24h, repeatedly filtered, washed and dried to obtain a gradient carbon coating layer construction material.

[0013] The advantages of the present invention are that citric acid is used as the carbon source, and a gradient carbon layer is formed through water bath evaporation and calcination process. The high conductivity and elasticity of carbon are utilized to suppress the volume change of silicon. At the same time, the porous structure increases the specific surface area and promotes electrolyte contact. After pickling to remove the calcium carbonate template, the hollow carbon shell formed further improves the cycle stability.

[0014] Preferably, step (5) the carbon nanotube conductive network is synthesized and prepared 100-200 mg of the gradient carbon coating layer building material of step (4), 80-100 mg of the nano-sized ball-milled waste silicon powder particles prepared in step (2) and 30-40 mM of hexadecyl ammonium bromide (CTAB) are added to deionized water and ultrasonically treated to obtain a suspension. CNTs are then added and stirred and dried. The mixture is sintered at high temperature in an N2 atmosphere to obtain a carbon nanotube conductive network.

[0015] The advantage of adopting the present invention is that, in this step, the silicon@carbon structure in the gradient carbon coating material provides stable core-shell support and cetyl ammonium bromide (CTAB) assists dispersion and high-temperature sintering to construct a three-dimensional conductive network of carbon nanotubes (CNTs) and silicon-carbon materials. The high conductivity of CNTs shortens the electron transmission path and enhances the overall conductivity of the material; the network structure effectively disperses stress, improves rate performance, and improves cycle life.

[0016] As a preference, step (6) preparation of graphene nanoribbon silicon-carbon composite material The carbon nanotube conductive network material of step (5) and the gradient carbon coating layer construction material (silicon-carbon composite material) of step (4) are added to deionized water in a mass ratio of 0.3~1:0.5~1 to obtain a solution, 1~2g of chitosan solution is added, and the precursor is obtained by centrifugal drying. Finally, the precursor is sintered at a high temperature under a protective atmosphere of N2 to obtain a graphene nanoribbon silicon-carbon composite material.

[0017] The advantage of adopting the present invention is that the nanoparticles are uniformly dispersed in the composite network composed of carbon nanotubes and graphene nanoribbons, the outer layer is further coated with graphene nanoribbons to form a multi-layer buffer structure, and the flexible structure of the silicon-carbon composite material further buffers the volume expansion of silicon while enhancing the mechanical strength of the material; the composite design synergistically improves energy density and low-temperature performance, providing a stable negative electrode material for long-lasting batteries.

[0018] In summary, the present invention has the following beneficial effects: 1. The advantage of the present invention is that no hazardous chemicals are required in this step. Photovoltaic waste silicon powder is industrial waste, low-cost and environmentally friendly. Through electronic-grade hydrochloric acid pickling and purification combined with ball milling under nitrogen protection, the photovoltaic waste silicon powder is converted into nano-scale silicon particles. The nano-processing significantly reduces the size of the silicon particles, effectively alleviating the problem of volume expansion, and providing a highly active silicon source for subsequent composite material preparation. 2. The advantage of the present invention is that, in this step, a calcium carbonate shell is constructed on the surface of the silicon particles through the precipitation reaction of sodium carbonate and calcium chloride solution. The core-shell structure forms a physical barrier, buffering the volume expansion of silicon and improving the structural stability of the material. At the same time, the neutral environment and porous properties of calcium carbonate facilitate electrolyte penetration, optimize lithium ion transmission efficiency, and provide an ideal substrate for subsequent carbon coating. 3. The advantages of the present invention are that citric acid is used as the carbon source, and a gradient carbon layer is formed through water bath evaporation and calcination. The high conductivity and elasticity of carbon are used to suppress the volume change of silicon. At the same time, the porous structure increases the specific surface area and promotes electrolyte contact. After acid washing to remove the calcium carbonate template, the hollow carbon shell formed further improves the cycle stability. 4. The advantages of the present invention are that the silicon@carbon structure in the gradient carbon coating material provides stable core-shell support and, through cetyl ammonium bromide (CTAB)-assisted dispersion and high-temperature sintering, constructs a three-dimensional conductive network of carbon nanotubes (CNTs) and silicon-carbon materials. The high conductivity of CNTs shortens the electron transmission path and enhances the overall conductivity of the material. The network structure effectively disperses stress, improves rate performance, and improves cycle life. 5. The advantage of adopting the present invention is that it is uniformly dispersed in the composite network composed of carbon nanotubes and graphene nanoribbons in the form of nanoparticles, and the outer layer is further coated with graphene nanoribbons to form a multi-layer buffer structure. The flexible structure of the silicon-carbon composite material further buffers the volume expansion of silicon and enhances the mechanical strength of the material. The composite design synergistically improves energy density and low-temperature performance, providing a stable negative electrode material for long-lasting batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a flow chart for preparing a high-capacity silicon-carbon composite negative electrode material according to the present invention; Figure 2 1 is an electron microscope image of the graphene nanoribbon silicon-carbon composite material prepared in Example 4 of the present invention; Figure 3 1 is a charge-discharge curve of the graphene nanoribbon silicon-carbon composite material prepared in Example 4 of the present invention; Figure 4 This is a cycle performance curve of the graphene nanoribbon silicon-carbon composite material prepared in Example 4 of the present invention. DETAILED DESCRIPTION

[0020] The following examples are provided to illustrate the present invention but are not intended to limit the scope of the present invention. Without departing from the spirit and substance of the present invention, modifications or substitutions made to the methods, steps or conditions of the present invention are within the scope of the present invention.

[0021] Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art. In addition, all the components and raw materials used in the examples are known commercial products.

[0022] Example 1

[0023] Step (1) Preparation of electronic grade hydrochloric acid Using trichloroethylene (TCE) and hydrofluoric acid (AHF) as raw materials, a fluorination reaction is carried out in a ratio of 1:2 to generate hydrogen chloride (HCl) as a byproduct. The reaction products are separated by a distillation tower, and high-purity hydrogen chloride gas is separated from the top of the tower and fed into a scrubbing tower. The scrubbing tower uses a circular hole block graphite falling film absorber with an operating pressure range of 1kPa and an operating temperature range of -25°C. The top temperature of the scrubbing tower is controlled at -35°C, the pressure is controlled at 0.9MPa, and the temperature difference is controlled at 0°C. In the scrubbing tower, the hydrogen chloride gas contacts and absorbs low-concentration hydrochloric acid from the bottom of the tail gas tower. After screening, electronic-grade hydrochloric acid is obtained. Step (2) Preparation of nano-sized ball-milled waste silicon powder particles First, the pretreated photovoltaic waste silicon powder is acid-washed and purified with the electronic-grade hydrochloric acid in step (1) for 20 hours, vacuum-dried for 10 hours, and then ball-milled for 2 hours under a protective atmosphere of N2 to obtain nano-sized ball-milled waste silicon powder particles; Step (3) Preparation of silicon@calcium carbonate core-shell structure material Take 0.5g of the nano-sized ball-milled waste silicon powder particles obtained in step (2) and calcium carbonate in a mass ratio of 1:1 to prepare 80mL of sodium carbonate solution and calcium chloride solution. Subsequently, the waste silicon powder particles are dispersed in 80mL of sodium carbonate solution to prepare a mixed solution Si / NaCO3. Subsequently, Si / NaCO3 is dripped into 80mL of calcium chloride solution while maintaining a constant temperature, with the water bath temperature at 30°C. Finally, the mixture is filtered, washed, and dried repeatedly to obtain a silicon@calcium carbonate core-shell structure material. Step (4) Preparation of gradient carbon coating layer According to a mass ratio of 1:1, citric acid and the silicon@calcium carbonate core-shell structure of step (3) were prepared in a mass ratio of 0.5:1, mixed and dispersed in an alcohol solution and stirred continuously to obtain a mixed solution, the mixed solution was placed in an 80°C water bath to evaporate the alcohol, and then the evaporated mixture was placed in a 500°C tube furnace for heat treatment and calcination for 2h, finally, the calcined mixture was pickled with dilute hydrochloric acid for 20h, repeatedly filtered, washed, and dried to obtain a gradient carbon coating layer construction material; Step (5) Synthesis and preparation of carbon nanotube conductive network 100 mg of the gradient carbon coating layer building material of step (4), 80 mg of the nano-sized ball-milled waste silicon powder particles prepared in step (2) and 30 mM of hexadecyl ammonium bromide (CTAB) were added to deionized water and ultrasonically treated to obtain a suspension. CNTs were then added and stirred and dried. The mixture was sintered at high temperature in an N2 atmosphere to obtain a carbon nanotube conductive network. Step (6) Preparation of graphene nanoribbon silicon-carbon composite material The carbon nanotube conductive network material of step (5) and the gradient carbon coating layer construction material (silicon-carbon composite material) of step (4) were added to deionized water in a mass ratio of 0.3:0.5 to obtain a solution, 1 g of chitosan solution was added, and the mixture was centrifugally dried to obtain a precursor. Finally, the mixture was sintered at a high temperature under a protective atmosphere of N2 to obtain a graphene nanoribbon silicon-carbon composite material.

[0024] Example 2

[0025] Step (1) Preparation of electronic grade hydrochloric acid Using trichloroethylene (TCE) and hydrofluoric acid (AHF) as raw materials, a fluorination reaction is carried out in a ratio of 2:3 to generate hydrogen chloride (HCl) as a byproduct. The reaction products are separated by a distillation tower, and high-purity hydrogen chloride gas is separated from the top of the tower and fed into a scrubbing tower. The scrubbing tower uses a circular hole block graphite falling film absorber with an operating pressure range of 10Pa and an operating temperature range of -10°C. The top temperature of the scrubbing tower is controlled at -30°C, the pressure is controlled at 1MPa, and the temperature difference is controlled at 2°C. In the scrubbing tower, the hydrogen chloride gas contacts and absorbs low-concentration hydrochloric acid from the bottom of the tail gas tower. After screening, electronic-grade hydrochloric acid is obtained. Step (2) Preparation of nano-sized ball-milled waste silicon powder particles First, the pretreated photovoltaic waste silicon powder is acid-washed and purified with the electronic-grade hydrochloric acid in step (1) for 21 hours, vacuum-dried for 11 hours, and then ball-milled for 3 hours under a protective atmosphere of N2 to obtain nano-sized ball-milled waste silicon powder particles; Step (3) Preparation of silicon@calcium carbonate core-shell structure material Take 1g of the nano-sized ball-milled waste silicon powder particles from step (2) and calcium carbonate in a mass ratio of 2:2 to prepare 90mL of sodium carbonate solution and calcium chloride solution. Subsequently, the waste silicon powder particles are dispersed in 90mL of sodium carbonate solution to prepare a mixed solution Si / NaCO3. Subsequently, Si / NaCO3 is dropped into 90mL of calcium chloride solution while maintaining a constant temperature, with the water bath temperature at 40°C. Finally, the mixture is filtered, washed, and dried repeatedly to obtain a silicon@calcium carbonate core-shell structure material. Step (4) Preparation of gradient carbon coating layer According to the mass ratio of 2:2, citric acid and the silicon@calcium carbonate core-shell structure of step (3) are prepared in a mass ratio of 1:2, mixed and dispersed in an alcohol solution and stirred continuously to obtain a mixed solution, the mixed solution is placed in a 90°C water bath to evaporate the alcohol, and then the evaporated mixture is placed in a 600°C tube furnace for heat treatment and calcination for 3 hours. Finally, the calcined mixture is pickled with dilute hydrochloric acid for 22 hours, repeatedly filtered, washed, and dried to obtain a gradient carbon coating layer construction material; Step (5) Synthesis and preparation of carbon nanotube conductive network 150 mg of the gradient carbon coating layer building material of step (4), 90 mg of the nano-sized ball-milled waste silicon powder particles prepared in step (2) and 35 mM of hexadecyl ammonium bromide (CTAB) were added to deionized water and ultrasonically treated to obtain a suspension. CNTs were then added and stirred and dried. The mixture was sintered at high temperature in an N2 atmosphere to obtain a carbon nanotube conductive network. Step (6) Preparation of graphene nanoribbon silicon-carbon composite material The carbon nanotube conductive network material of step (5) and the gradient carbon coating layer construction material (silicon-carbon composite material) of step (4) were added to deionized water in a mass ratio of 0.5:0.7 to obtain a solution, 1.5 g of chitosan solution was added, and the mixture was centrifugally dried to obtain a precursor. Finally, the mixture was sintered at high temperature under a protective atmosphere of N2 to obtain a graphene nanoribbon silicon-carbon composite material.

[0026] Example 3

[0027] Step (1) Preparation of electronic grade hydrochloric acid Using trichloroethylene (TCE) and hydrofluoric acid (AHF) as raw materials, a fluorination reaction is carried out in a ratio of 4:6 to generate hydrogen chloride (HCl) as a byproduct. The reaction products are separated by a distillation tower, and high-purity hydrogen chloride gas is separated from the top of the tower and fed into a scrubbing tower. The scrubbing tower uses a circular hole block graphite falling film absorber with an operating pressure range of 40 Pa and an operating temperature range of 20°C. The top temperature of the scrubbing tower is controlled at -28°C, the pressure is controlled at 1.1 MPa, and the temperature difference is controlled at 3°C. In the scrubbing tower, the hydrogen chloride gas contacts and absorbs low-concentration hydrochloric acid from the bottom of the tail gas tower. After screening, electronic-grade hydrochloric acid is obtained. Step (2) Preparation of nano-sized ball-milled waste silicon powder particles First, the pretreated photovoltaic waste silicon powder is acid-washed and purified with the electronic-grade hydrochloric acid in step (1) for 22 hours, vacuum-dried for 12 hours, and then ball-milled for 4 hours under a protective atmosphere of N2 to obtain nano-sized ball-milled waste silicon powder particles; Step (3) Preparation of silicon@calcium carbonate core-shell structure material Take 1.5g of the nano-sized ball-milled waste silicon powder particles obtained in step (2) and calcium carbonate in a mass ratio of 3:3 to prepare 100mL of sodium carbonate solution and calcium chloride solution. Subsequently, the waste silicon powder particles are dispersed in 100mL of sodium carbonate solution to prepare a mixed solution Si / NaCO3. Subsequently, Si / NaCO3 is dripped into 100mL of calcium chloride solution while maintaining a constant temperature, with the water bath temperature at 50°C. Finally, the mixture is repeatedly filtered, washed, and dried to obtain a silicon@calcium carbonate core-shell structure material. Step (4) Preparation of gradient carbon coating layer According to the mass ratio of 3:3, citric acid and the silicon@calcium carbonate core-shell structure of step (3) were prepared in a mass ratio of 1.5:2.5, respectively, and dispersed in an alcohol solution with continuous stirring after mixing to obtain a mixed solution. The mixed solution was placed in a water bath at 100°C to evaporate the alcohol, and then the evaporated mixture was placed in a tube furnace at 700°C for heat treatment and calcination for 4 hours. Finally, the calcined mixture was pickled with dilute hydrochloric acid for 23 hours, and repeatedly filtered, washed, and dried to obtain a gradient carbon coating layer construction material; Step (5) Synthesis and preparation of carbon nanotube conductive network 200 mg of the gradient carbon coating layer building material of step (4), 95 mg of the nano-sized ball-milled waste silicon powder particles prepared in step (2) and 40 mM of hexadecyl ammonium bromide (CTAB) were added to deionized water and ultrasonically treated to obtain a suspension. CNTs were then added and stirred and dried. The mixture was sintered at high temperature in an N2 atmosphere to obtain a carbon nanotube conductive network. Step (6) Preparation of graphene nanoribbon silicon-carbon composite material The carbon nanotube conductive network material of step (5) and the gradient carbon coating layer construction material (silicon-carbon composite material) of step (4) were added to deionized water in a mass ratio of 0.7:0.7 to obtain a solution, 1.75 g of chitosan solution was added, and the mixture was centrifugally dried to obtain a precursor. Finally, the mixture was sintered at high temperature under a protective atmosphere of N2 to obtain a graphene nanoribbon silicon-carbon composite material.

[0028] Example 4

[0029] Step (1) Preparation of electronic grade hydrochloric acid Using trichloroethylene (TCE) and hydrofluoric acid (AHF) as raw materials, a fluorination reaction is carried out in a ratio of 5:7 to generate hydrogen chloride (HCl) as a byproduct. The reaction products are separated by a distillation tower, and high-purity hydrogen chloride gas is separated from the top of the tower and fed into a scrubbing tower. The scrubbing tower uses a circular hole block graphite falling film absorber with an operating pressure range of 60kPa and an operating temperature range of 80°C. The top temperature of the scrubbing tower is controlled at -25°C, the pressure is controlled at 1.1MPa, and the temperature difference is controlled at 5°C. In the scrubbing tower, the hydrogen chloride gas contacts and absorbs low-concentration hydrochloric acid from the bottom of the tail gas tower. After screening, electronic-grade hydrochloric acid is obtained. Step (2) Preparation of nano-sized ball-milled waste silicon powder particles First, the pretreated photovoltaic waste silicon powder is acid-washed and purified with the electronic-grade hydrochloric acid in step (1) for 24 hours, vacuum-dried for 12 hours, and then ball-milled for 3 hours under a protective atmosphere of N2 to obtain nano-sized ball-milled waste silicon powder particles; Step (3) Preparation of silicon@calcium carbonate core-shell structure material Take 0.5g of the nano-sized ball-milled waste silicon powder particles from step (2) and calcium carbonate in a mass ratio of 2:4 to prepare 95mL of sodium carbonate solution and calcium chloride solution. Then, disperse the waste silicon powder particles in 95mL of sodium carbonate solution to prepare a mixed solution Si / NaCO3. Then, drop Si / NaCO3 into 100mL of calcium chloride solution while maintaining a constant temperature, with the water bath temperature at 45°C. Finally, filter, wash and dry repeatedly to obtain a silicon@calcium carbonate core-shell structure material. Step (4) Preparation of gradient carbon coating layer According to the mass ratio of 2:5, citric acid and the silicon@calcium carbonate core-shell structure of step (3) were prepared in a mass ratio of 0.5:1.25, mixed and dispersed in an alcohol solution and stirred continuously to obtain a mixed solution, the mixed solution was placed in an 85°C water bath to evaporate the alcohol, and then the evaporated mixture was placed in a 700°C tube furnace for heat treatment and calcination for 4 hours. Finally, the calcined mixture was pickled with dilute hydrochloric acid for 24 hours, repeatedly filtered, washed, and dried to obtain a gradient carbon coating layer construction material; Step (5) Synthesis and preparation of carbon nanotube conductive network 100 mg of the gradient carbon coating layer building material of step (4), 100 mg of the nano-sized ball-milled waste silicon powder particles prepared in step (2) and 40 mM of hexadecyl ammonium bromide (CTAB) were added to deionized water and ultrasonically treated to obtain a suspension. CNTs were then added and stirred and dried. The mixture was sintered at high temperature in an N2 atmosphere to obtain a carbon nanotube conductive network. Step (6) Preparation of graphene nanoribbon silicon-carbon composite material The carbon nanotube conductive network material of step (5) and the gradient carbon coating layer construction material (silicon-carbon composite material) of step (4) were added to deionized water in a mass ratio of 0.5:1 to obtain a solution, 2 g of chitosan solution was added, and the mixture was centrifugally dried to obtain a precursor. Finally, the mixture was sintered at a high temperature under a protective atmosphere of N2 to obtain a graphene nanoribbon silicon-carbon composite material.

[0030] Comparative Example 1

[0031] Step (1) Preparation of electronic grade hydrochloric acid Using trichloroethylene (TCE) and hydrofluoric acid (AHF) as raw materials, a fluorination reaction is carried out in a ratio of 2:3 to generate hydrogen chloride (HCl) as a byproduct. The reaction products are separated by a distillation tower, and high-purity hydrogen chloride gas is separated from the top of the tower and fed into a scrubbing tower. The scrubbing tower uses a circular hole block graphite falling film absorber with an operating pressure range of 10Pa and an operating temperature range of -10°C. The top temperature of the scrubbing tower is controlled at -30°C, the pressure is controlled at 1MPa, and the temperature difference is controlled at 2°C. In the scrubbing tower, the hydrogen chloride gas contacts and absorbs low-concentration hydrochloric acid from the bottom of the tail gas tower. After screening, electronic-grade hydrochloric acid is obtained. Step (2) Preparation of nano-sized ball-milled waste silicon powder particles First, the pretreated photovoltaic waste silicon powder is acid-washed and purified with the electronic-grade hydrochloric acid in step (1) for 21 hours, vacuum-dried for 11 hours, and then ball-milled for 3 hours under a protective atmosphere of N2 to obtain nano-sized ball-milled waste silicon powder particles; Step (3) Preparation of gradient carbon coating layer According to a mass ratio of 2:2, citric acid and silicon@calcium carbonate core-shell structure with a mass ratio of 1:2 were prepared respectively, and after mixing, they were dispersed in an alcohol solution and continuously stirred to obtain a mixed solution. The mixed solution was placed in a 90°C water bath to evaporate the alcohol, and then the evaporated mixture was placed in a 600°C tube furnace for heat treatment and calcination for 3 hours. Finally, the calcined mixture was pickled with dilute hydrochloric acid for 22 hours, repeatedly filtered, washed, and dried to obtain a gradient carbon coating layer construction material; Step (4) Synthesis and preparation of carbon nanotube conductive network 150 mg of the gradient carbon coating layer building material of step (3), 90 mg of the nano-sized ball-milled waste silicon powder particles prepared in step (2) and 35 mM of hexadecyl ammonium bromide (CTAB) were added to deionized water and ultrasonically treated to obtain a suspension. CNTs were then added and stirred and dried. The mixture was sintered at high temperature in an N2 atmosphere to obtain a carbon nanotube conductive network. Step (5) Preparation of graphene nanoribbon silicon-carbon composite material The carbon nanotube conductive network material of step (4) and the gradient carbon coating layer construction material (silicon-carbon composite material) of step (4) were added to deionized water in a mass ratio of 0.5:0.7 to obtain a solution, 1.5 g of chitosan solution was added, and the mixture was centrifugally dried to obtain a precursor. Finally, the mixture was sintered at a high temperature under a protective atmosphere of N2 to obtain a graphene nanoribbon silicon-carbon composite material.

[0032] Comparative Example 2

[0033] Step (1) Preparation of nano-sized ball-milled waste silicon powder particles First, the pre-treated photovoltaic waste silicon powder was acid-washed and purified with hydrochloric acid for 24 hours, vacuum-dried for 12 hours, and then ball-milled for 3 hours under a nitrogen atmosphere to obtain nano-sized ball-milled waste silicon powder particles. Step (2) Preparation of silicon@calcium carbonate core-shell structure material Take 0.5g of the nano-sized ball-milled waste silicon powder particles from step (1) and calcium carbonate in a mass ratio of 1:5 to prepare 100mL of sodium carbonate solution and calcium chloride solution. Then, disperse the waste silicon powder particles in 100mL of sodium carbonate solution to prepare a mixed solution Si / NaCO3. Then, drop Si / NaCO3 into 100mL of calcium chloride solution while maintaining a constant temperature, with the water bath temperature at 45°C. Finally, filter, wash and dry repeatedly to obtain a silicon@calcium carbonate core-shell structure material. Step (3) Preparation of gradient carbon coating layer According to the mass ratio of 2:5, citric acid and silicon@calcium carbonate core-shell structure with a mass ratio of 0.5:1.25 were prepared respectively, and the mixture was dispersed in an alcohol solution with continuous stirring to obtain a mixed solution. The mixed solution was placed in an 85°C water bath to evaporate the alcohol, and then the evaporated mixture was placed in a 600°C tube furnace for heat treatment and calcination for 4 hours. Finally, the calcined mixture was pickled with dilute hydrochloric acid for 24 hours, repeatedly filtered, washed, and dried to obtain a gradient carbon coating layer construction material; Step (4) Preparation of graphene nanoribbon silicon-carbon composite material The carbon nanotube conductive network material and the gradient carbon coating layer construction material (silicon-carbon composite material) of step (4) were added to deionized water in a mass ratio of 0.5:1 to obtain a solution, 2 g of chitosan solution was added, and the mixture was centrifugally dried to obtain a precursor. Finally, the mixture was sintered at a high temperature under a protective atmosphere of N2 to obtain a graphene nanoribbon silicon-carbon composite material.

[0034] Comparison of detection experiments: The high-capacity silicon-carbon composite negative electrode materials obtained in Examples 1 to 4 and Comparative Example Products 1 and 2 were tested. The specific testing methods are as follows: Constant current charge and discharge cycle method The LAND battery test system was used to conduct charge and discharge tests and rate performance tests on button lithium-ion batteries, with the discharge cut-off voltage set at 0.005V and the charge cut-off voltage set at 2V.

[0035] Electrochemical performance characterization After aging the button cells for 12 hours, the electrochemical performance was tested using a Xinwei battery performance tester. The specific test steps are as follows: constant current discharge conditions: 0.1C, cutoff voltage 0.005V, 0.05C, cutoff voltage 0.005V, 0.02C, cutoff voltage 0.005V, rest period: 5 minutes; constant current charge conditions: 0.1C, cutoff voltage 2.0V, rest period: 5 minutes. All tests were completed at 25°C. After undergoing the above tests, the button cells were then subjected to cycle performance testing using a Xinwei battery performance tester. The specific test steps are as follows: constant current discharge: 0.1C, cutoff voltage 0.005V, rest: 5 minutes; constant current charge conditions: 0.1C, cutoff voltage 2.0V, rest: 5 minutes, and the charge and discharge steps were repeated. All tests were completed at 25°C.

[0036] Electrochemical impedance spectroscopy (EIS) Electrochemical impedance spectroscopy (EIS) is an important technique for studying electrochemical systems. It applies small-amplitude sinusoidal AC potential waves of different frequencies to the electrochemical system and measures the ratio of the AC potential to the current signal. This allows the user to infer the internal equivalent circuit of the battery, analyze the dynamic process and mechanism of the battery system, and understand the charge transfer performance of the material. The impedance value is generally 0-300Ω. If the test value is low, then the resistance is low and the conductivity of the prepared negative electrode material is better. If the test value is high, then the opposite is true.

[0037] Table 1 Initial charge and discharge specific capacity test results

[0038] As can be seen from Table 1, nano-silicon is small in size and more prone to agglomeration. During the lithium insertion process, the volume expansion is aggravated, causing the capacity to decay sharply. However, Example 4, in which an amorphous carbon coating layer is formed after the electrode surface is coated and modified, has excellent charge specific capacity and the initial charge and discharge efficiency is also improved.

[0039] Table 2 Constant current charge and discharge cycle capacity retention test results

[0040] Table 2 constant current charge and discharge cycle capacity retention test and Figure 3 The results show that Example 4 is the best and Comparative Example 2 is the worst. In Example 4, the charge capacity after 100 cycles is 2091 mAh·g -1 , the capacity retention rate is 93.81%, showing good cycle stability, which is due to the structural stability of the material.

[0041] Table 3 Electrochemical impedance spectroscopy (EIS)

[0042] As shown in Table 3, Example 4 is the best and Comparative Example 2 is the worst. In Example 4, the impedance value is 50Ω, indicating that the charge transfer between the electrode material and the electrolyte of the prepared negative electrode material is more rapid, the electrochemical reaction rate is faster, and its conductivity is better. The impedance value of Comparative Example 2 is 85Ω, indicating that its charge transfer process encounters greater resistance and its conductivity is poor.

[0043] This specific embodiment is merely an explanation of the present invention and does not limit the present invention. After reading this specification, a person skilled in the art may make non-creative modifications to this embodiment as needed. However, as long as it is within the scope of the claims of the present invention, it is protected by patent law.

Claims

1. A preparation method of a high-capacity silicon-carbon composite negative electrode material, characterized in that: include: Preparation of electronic grade hydrochloric acid, preparation of photovoltaic waste silicon powder by ball milling, preparation of silicon@calcium carbonate core-shell structure materials, preparation of gradient carbon coating layer construction, synthesis and preparation of carbon nanotube conductive network, and preparation of graphene nanoribbon silicon-carbon composite materials.

2. The method of claim 1, wherein: Step (1) Preparation of electronic grade hydrochloric acid Using trichloroethylene (TCE) and hydrofluoric acid (AHF) as raw materials, a fluorination reaction is carried out in a certain ratio to generate hydrogen chloride (HCl) as a by-product. The reaction products are separated by a distillation tower, and high-purity hydrogen chloride gas is separated from the top of the tower and fed into a scrubbing tower. The scrubbing tower uses a circular hole block graphite falling film absorber. The top temperature of the scrubbing tower is controlled below zero. In the scrubbing tower, the hydrogen chloride gas contacts and absorbs low-concentration hydrochloric acid from the bottom of the tail gas tower. After screening, electronic-grade hydrochloric acid is obtained. Step (2) Preparation of nano-sized ball-milled waste silicon powder particles First, the pre-treated photovoltaic waste silicon powder is acid-washed and purified with the electronic-grade hydrochloric acid in step (1), and vacuum-dried for a period of time, and then ball-milled for a period of time under a protective atmosphere of N2 to obtain nano-sized ball-milled waste silicon powder particles; Step (3) Preparation of silicon@calcium carbonate core-shell structure material A small amount of nano-sized ball-milled waste silicon powder particles from step (2) is taken and mixed with calcium carbonate to prepare a certain amount of sodium carbonate solution and calcium chloride solution in a certain mass ratio. Subsequently, the waste silicon powder particles are dispersed in a certain amount of sodium carbonate solution to prepare a mixed solution Si / NaCO3. Subsequently, Si / NaCO3 is dripped into a certain amount of calcium chloride solution while maintaining a constant temperature and a suitable water bath temperature. Finally, the mixture is repeatedly filtered, washed, and dried to obtain a silicon@calcium carbonate core-shell structure material. Step (4) Preparation of gradient carbon coating layer According to a certain mass ratio, a certain amount of citric acid and the silicon@calcium carbonate core-shell structure of step (3) are prepared respectively, and the mixture is dispersed in an alcohol solution and continuously stirred to obtain a mixed solution. The mixed solution is placed in a water bath at a certain temperature to evaporate the alcohol, and then the evaporated mixture is placed in a tubular furnace at a certain temperature for heat treatment and calcination for a period of time. Finally, the calcined mixture is pickled with dilute hydrochloric acid for a period of time, repeatedly filtered, washed and dried to obtain a gradient carbon coating layer construction material; Step (5) Preparation of carbon nanotube conductive network synthesis The gradient carbon coating layer construction material of step (4), a certain amount of nano-sized ball-milled waste silicon powder particles prepared in step (2) and an appropriate amount of hexadecyl ammonium bromide (CTAB) are added together in deionized water and ultrasonically treated to obtain a suspension, and then CNTs are added and continued to be stirred and dried, and sintered at high temperature in an N2 atmosphere to obtain a carbon nanotube conductive network; Step (6) Preparation of graphene nanoribbon silicon-carbon composite material According to a certain ratio, the carbon nanotube conductive network material of step (5) and the gradient carbon coating layer construction material (silicon-carbon composite material) of step (4) are added to deionized water to obtain a solution, an appropriate amount of chitosan solution is added, and the precursor is obtained by centrifugal drying. Finally, the precursor is sintered at a high temperature under a protective atmosphere of N2 to obtain a graphene nanoribbon silicon-carbon composite material.

3. The method of claim 2, wherein: Step (1) Preparation of electronic grade hydrochloric acid Using trichloroethylene (TCE) and hydrofluoric acid (AHF) as raw materials, a fluorination reaction is carried out in a ratio of 1-5:2-7 to generate hydrogen chloride (HCl) as a by-product. The reaction products are separated by a distillation tower, and high-purity hydrogen chloride gas is separated from the top of the tower and fed into a scrubbing tower. The scrubbing tower adopts a circular hole block graphite falling film absorber with an operating pressure range of 0-60kPa and an operating temperature range of -25-80℃. The top temperature of the scrubbing tower is controlled at -35--25℃, the pressure is controlled at 0.9-1.1MPa, and the temperature difference is controlled at 0-5℃. In the scrubbing tower, the hydrogen chloride gas contacts and absorbs low-concentration hydrochloric acid from the bottom of the tail gas tower. After screening, electronic-grade hydrochloric acid is obtained.

4. The method of claim 3 , wherein: Step (2) Preparation of nano-sized ball-milled waste silicon powder particles First, the pretreated photovoltaic waste silicon powder is acid-washed and purified with the electronic-grade hydrochloric acid in step (1) for 20 to 24 hours, vacuum-dried for 10 to 12 hours, and then ball-milled for 2 to 4 hours under a protective atmosphere of N2 to obtain nano-sized ball-milled waste silicon powder particles.

5. The method of claim 4 , wherein: Step (3) Preparation of silicon@calcium carbonate core-shell structure material Take 0.5~2g of the nano-sized ball-milled waste silicon powder particles in step (2) and calcium carbonate in a mass ratio of 1~5:1~5 to prepare 80~100mL of sodium carbonate solution and calcium chloride solution. Then, disperse the waste silicon powder particles in 80~100mL of sodium carbonate solution to prepare a mixed solution Si / NaCO3. Then, drop Si / NaCO3 into 80~100mL of calcium chloride solution while maintaining a constant temperature. The water bath temperature is at 30~50℃. Finally, filter, wash and dry repeatedly to obtain a silicon@calcium carbonate core-shell structure material.

6. The method of claim 5, wherein: Step (4) Preparation of gradient carbon coating layer According to the mass ratio of 1~5:1~5, citric acid and the silicon@calcium carbonate core-shell structure of step (3) are prepared in a mass ratio of 0.5~2:1~3, mixed and dispersed in an alcohol solution and continuously stirred to obtain a mixed solution, the mixed solution is placed in a water bath at 80~100℃ to evaporate the alcohol, and then the evaporated mixture is placed in a tube furnace at 500~800℃ for heat treatment and calcination for 2~5h. Finally, the calcined mixture is pickled with dilute hydrochloric acid for 20~24h, repeatedly filtered, washed and dried to obtain a gradient carbon coating layer construction material.

7. The method of claim 6, wherein: Step (5) Synthesis and preparation of carbon nanotube conductive network 100-200 mg of the gradient carbon coating layer building material of step (4), 80-100 mg of the nano-sized ball-milled waste silicon powder particles prepared in step (2) and 30-40 mM of hexadecyl ammonium bromide (CTAB) are added to deionized water and ultrasonically treated to obtain a suspension. CNTs are then added and stirred and dried. The mixture is sintered at high temperature in an N2 atmosphere to obtain a carbon nanotube conductive network.

8. The method of claim 7, wherein: Step (6) Preparation of graphene nanoribbon silicon-carbon composite material The carbon nanotube conductive network material of step (5) and the gradient carbon coating layer construction material (silicon-carbon composite material) of step (4) are added to deionized water in a mass ratio of 0.3~1:0.5~1 to obtain a solution, 1~2g of chitosan solution is added, and the precursor is obtained by centrifugal drying. Finally, the precursor is sintered at a high temperature under a protective atmosphere of N2 to obtain a graphene nanoribbon silicon-carbon composite material.

Citation Information

Cited By

  • A method for preparing a porous silicon-carbon negative electrode by using photovoltaic waste silicon and calcium carbonate template method and application

    CN122444189A